Longer-term impacts of mentoring, educational services, and incentives to learn: evidence from a randomized trial - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2010)
This paper is the first to use a randomized trial in the US to analyze the short- and long-term educational and employment impacts of an after-school program, the Quantum Opportunity Program, that offered disadvantaged high-school youth: mentoring, educational services, and financial rewards with the objective to improve high-school graduation and post-secondary schooling enrollment. Average impacts reveal that the hefty beneficial educational outcomes quickly faded away. Heterogeneity matters. While encouraging results are found for the younger youth; detrimental long-lived outcomes for males suggest that extrinsic rewards may be crowding out intrinsic motivation. Evidence by sites' funding source, which led to implementation differences, supports this hypothesis.
Keywords: C93; I21; I22; I28; J24; 330; Short-; medium- and long-term effects; after-school programs; intrinsic and extrinsic motivation; educational and employment outcomes; Bildungspolitik; Coaching; Jugendliche; Bildungsverhalten; Motivation; Bildungsniveau; Beschäftigungseffekt; USA